Hyperechoic breast images: all that glitters is not gold! - Gabrielle Journo; Guillaume Bataillon; Raphael Benchimol; Asma Bekhouche; Chloe Dratwa; Delphine Sebbag-Sfez; Anne Tardivon; Fabienne Thibault; Catherine Ala-Eddine; Pascal Chérel; Caroline Malhaire (Insights into Imaging, 2018)
Abstract Hyperechogenicity is a sign classically reported to be in favour of a benign lesion and can be observed in many types of benign breast lesions such as hamartoma, lipoma, angiolipoma, haemangioma, haematoma, fat necrosis, fibrosis and galactocele, among others. However, some rare malignant breast lesions can also present a hyperechoic appearance. Most of these hyperechoic malignant lesions present other characteristics that are more typically suggestive of malignancy such as posterior shadowing, a more vertical axis or irregular margins that help to guide the diagnosis. Post magnetic resonance imaging, second-look ultrasound may visualise hyperechoic malignant lesions that would not have been identified at first sight and radiologists must know how to recognise these lesions. Teaching Points • Some rare malignant breast lesions can present a hyperechoic appearance. • Malignant lesions present other characteristics that are suggestive of malignancy. • An echogenic mass with fat density on mammography does not require biopsy.